The Europeanization of Gender Equality Policies - Lombardo, Emanuela. author. aut Link
XIX, 242 p.
Keywords: A discursive-sociological approach to the Europeanization of gender and other equality policies. Using largely unpublished empirical data covering twenty-nine European countries this book adopts a pluralistic perspective to explore the complex and often divergent gender and other equality policy outputs of Europeanization.